Growing pains of a data repository: GRIIDC's evolution from environmental disaster rapid response to promoting FAIR data - Rossi, Rosalie R.; LeBel, Deborah A.; Gibeaut, James (Frontiers in Climate, 2022)
GRIIDC is a multidisciplinary data repository created in the aftermath of the Deepwater Horizon oil spill. Development of the repository occurred even as researchers collected post-spill data, and as a result, the data management system initially focused on the ingestion of data and metadata. Data sharing was not as prevalent as it is currently, and many researchers were not familiar with data sharing and data organization best practices. From this challenging beginning, over the decade since the Deepwater Horizon oil spill, GRIIDC has improved the data management system, the data curation process, and the training of researchers which has enhanced the ease of submission and quality of data submitted. The GRIIDC system has also evolved to prioritize the implementation of FAIR data principles to ensure the data are findable, accessible, interoperable, and reusable. All data are issued digital object identifiers (DOIs) through DataCite and are findable via GRIIDC’s data search page, DataONE, and Google Dataset Search. Each dataset has a dataset landing page where the data and metadata can be accessed. The data curation process includes subject matter experts who ensure that dataset files can be reused by verifying they are not corrupt, are in non-proprietary formats, are complete, and are well-documented with ISO 19115-2 metadata. GRIIDC is continuously striving to add FAIR principles to the system. Although there are still many challenges including quality of data and metadata received, funding limitations, and program priorities, GRIIDC must always continue to improve meeting user needs while implementing FAIR data principles.